Cellulose Triacetate-Based Mixed-Matrix Membranes with MXene 2D Filler-CO2/CH4 Separation Performance and Comparison with TiO2-Based 1D and 0D Fillers - Regmi, Chhabilal; Azadmanjiri, Jalal; Mishra, Vipin; Sofer, Zdeněk; Ashtiani, Saeed; Friess, Karel (Membranes, 2022)
Mixed-matrix membranes (MMMs) possess the unique properties and inherent characteristics of their component polymer and inorganic fillers, or other possible types of additives. However, the successful fabrication of compact and defect-free MMMs with a homogeneous filler distribution poses a major challenge, due to poor filler/polymer compatibility. In this study, we use two-dimensional multi-layered Ti3C2Tx MXene nanofillers to improve the compatibility and CO2/CH4 separation performance of cellulose triacetate (CTA)-based MMMs. CTA-based MMMs with TiO2-based 1D (nanotubes) and 0D (nanofillers) additives were also fabricated and tested for comparison. The high thermal stability, compact homogeneous structure, and stable long-term CO2/CH4 separation performance of the CTA-2D samples suggest the potential application of the membrane in bio/natural gas separation. The best results were obtained for the CTA-2D sample with a loading of 3 wt.%, which exhibited a 5-fold increase in CO2 permeability and 2-fold increase in CO2/CH4 selectivity, compared with the pristine CTA membrane, approaching the state-of-the-art Robeson 2008 upper bound. The dimensional (shape) effect on separation performance was determined as 2D > 1D > 0D. The use of lamellar stacked MXene with abundant surface-terminating groups not only prevents the aggregation of particles but also enhances the CO2 adsorption properties and provides additional transport channels, resulting in improved CO2 permeability and CO2/CH4 selectivity.
Keywords: MXene; TiO2 nanotube; cellulose triacetate; mixed-matrix membrane; TiO2 nanoparticles; gas separation